The influence of defendant body size and defendant gender on mock juror decision-making - Brown, D. (Dylan) (Cogent Psychology, 2019)
Objectives: These studies were designed to extend the limited psycho-legal literature on weight bias in juror decision-making. Methods: In two studies, students (N = 208) and online community participants (N = 199) read a fabricated theft trial transcript in which we varied the defendant’s weight (overweight, average weight, underweight) and gender (man, woman). Participants then made verdict decisions and completed a measure of positive attitudes toward obesity. Results: In Study 1, the overweight condition featured a fairly even verdict split, while the underweight and average weight conditions featured a higher proportion of guilty verdicts than not guilty verdicts. In Study 2, among those with more positive attitudes toward obesity, the average weight condition yielded a greater likelihood of a guilty verdict as compared to the underweight condition. Thus, Study 1 revealed relative leniency toward a defendant who was overweight, whereas Study 2 revealed more lenient decisions for a defendant who was underweight (as a function of attitudes). There were no significant gender effects. Conclusions: Findings are inconsistent with bias against obesity shown in the extant literature, which might be attributable to idiosyncrasies of the case material used. In general, results indicate that defendant weight is a source of bias among mock jurors. Future researchers examining weight bias in the courtroom should consider the potential effects of crime congruency by exploring defendant weight in different types of criminal cases